Migracje jako akt zbiorowy. Studium przypadków - Adamczyk, Anita (Studia Polityczne, 2024)
The 21st century became a period of mass migration, which had to do with the „shrinking of the world” through globalization, the development of means of transport and communication. In 2015 and 2016, Europe experienced its first migration crisis. The next occurred in 2021 and 2022. Forecasts for Europe in this regard are not optimistic. from which it can be concluded that we will experience further crowds of migrants at the external borders of the EU. The purpose of this article is to analyze migration to EU countries in the context of a collective act. In it, the thesis is put forward that being in a crowd increases the chances of the migrants’ intentions being realized. The article is divided into three parts. In the first, it analyzed the processes of psychological behavior in a crowd based mainly on Gustav Le Bon’s theory. Next, the migration crises of 2015 and 2021 were explored in the context of the migrant crowd. In turn, the last part deals with the so-called the „Caravan of Light” that is, the attempt by Syrians from Turkey to the EU to undertake collective migration in 2022.